The role of exosomal miRNA in nonalcoholic fatty liver disease. Issue 4 (8th February 2022) - Mahmoudi, Ali; Butler, Alexandra E.; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract: Nonalcoholic fatty liver disease (NAFLD) impacts more than one‐third of the population and is linked with other metabolic diseases. The term encompasses a wide spectrum of diseases, from modest steatosis to nonalcoholic steatohepatitis, fibrosis and, ultimately, cirrhosis with the potential for development of hepatocellular carcinoma. Currently, available methods for diagnosing NAFLD are invasive or lack accuracy, and monitoring to determine response to therapeutic interventions is challenging. Exosomes are nano‐scaled extracellular vesicles that are secreted by a variety of cells. They convey proteins, mRNA, miRNA, and other bioactive molecules between cells and are involved in an extensive range of biological processes, particularly cell‐cell communication. Several reports suggest that exosomes mediate miRNAs and, thus, they have potential clinical utility for diagnosis, prognosis, and therapeutics in liver diseases. In view of the vital role of exosomal microRNA in disease, we here synthesized current knowledge about the biogenesis of exosomal miRNA and exosome‐mediated microRNA transfer. We then discuss the potential of exosomal miRNA in diagnosis and therapeutics of NAFLD. Abstract : Several reports suggest that exosomes mediate miRNAs and, thus, they have potential clinical utility for diagnosis, prognosis, and therapeutics in liver diseases. In view of the vital role of exosomal microRNA in disease, we here synthesized current knowledge about the biogenesis of exosomal miRNA and exosome‐mediated microRNA transfer. We then discuss the potential of exosomal miRNA in diagnosis and therapeutics of nonalcoholic fatty liver disease.